Strategi Kepolisian Resor Jayawijaya Dalam Menekan Tindak Pidana Pencurian: Studi Kasus Tindak Pidana 3c; Curat, Curas Dan Curanmor - Irwanto Irwanto; Ali Maskur (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2024)
The focus of this research is to explain the strategy of the Jayawijaya Resor Police Office in reducing the number of criminal offenses in the Jayawijaya jurisdiction. Jayawijaya crime data in 2022 there are 129 cases motor vehicle theft, 38 cases theft with aggravation and 19 cases theft with violence. Anticipation activities, field actions, and punishment are carried out so that the number of crimes can be suppressed. Qualitative research with data collection techniques through documentation, interviews and observations. The results of the study are the existence of a special strategy in suppressing crime in collaboration with the community, routine raids in several vulnerable areas and the importance of witness and community participation in suppressing crime in the Jayawijaya Regional Police jurisdiction.